Sistemas bentonitas/tiabendazol- ensaios interativos e de emissão controlada - Cavalcanti, Graycyelle Rodrigues da Silva (2017)
Systems based on clay minerals/drug for application as drug delivery have been studied because of their physical and chemical properties such as good ion exchange, capacity of intercalation, biocompatibility and low toxicity, furthermore their use in pharmaceutical products as excipients and active agents. Therefore in this work, a bentonite sample, which had montmorillonite as principal constituent, was modified through ion exchange with sodium (BentNa), calcium (BentCa) and magnesium (BentMg) and the obtained solids were applied for sorption of thiabendazole (TBZ) for possible use as controlled release systems. Precursor, exchanged and hybrid bentonites were characterized by X-ray diffraction, infrared spectroscopy, solid state UV-Vis spectroscopy, CHN elemental analysis, thermogravimetry and transmission electron microscopy (TEM). In the study of the The interactions between the solids with thiabendazole were investigated in function of parameters such as pH, contact time and initial concentration of drug. The better conditions in the thiabendazole loading tests were at pH 1.4 and 45 min at 2000 mg L-1 thiabendazole for BentNa and 105 min and 1300 mg L-1 for BentCa and BentMg, which conditions were adopted and resulted in maximum adsorbed quantities of TBZ of 164.4; 152.3 and 133.3 mg g-1 for BentNa, BentCa and BentMg, respectively. The XRD patterns suggested the formation of intercalation hybrid with basal spacings of 1,42; 1,41 e 1,39 nm for BentNa, BentCa e BentMg, respectively. The obtained emission profile for the bentonite/TBZ hybrids were similar in simulated body fluids, and their data were fitted to Korsmeyer-Peppas kinetic model.